Rabies post-exposure healthcare-seeking behaviors and perceptions: Results from a knowledge, attitudes, and practices survey, Uganda, 2013. - Sarah C Bonaparte; Laura Adams; Barnabas Bakamutumaho; Galileu Barbosa Costa; Julie M Cleaton; Amy T Gilbert; Modupe Osinubi; Emily G Pieracci; Sergio Recuenco; Victor Tugumizemu; Joseph Wamala; Ryan M Wallace (PLoS ONE)
Background Rabies is a viral disease of animals and people causing fatal encephalomyelitis if left untreated. Although effective pre- and post-exposure vaccines exist, they are not widely available in many endemic countries within Africa. Since many individuals in these countries remain at risk of infection, post-exposure healthcare-seeking behaviors are crucial in preventing infection and warrant examination. Methodology A rabies knowledge, attitudes, and practices survey was conducted at 24 geographically diverse sites in Uganda during 2013 to capture information on knowledge concerning the disease, response to potential exposure events, and vaccination practices. Characteristics of the surveyed population and of the canine-bite victim sub-population were described. Post-exposure healthcare-seeking behaviors of canine-bite victims were examined and compared to the related healthcare-seeking attitudes of non-bite victim respondents. Wealth scores were calculated for each household, rabies knowledge was scored for each non-bitten survey respondent, and rabies exposure risk was scored for each bite victim. Logistic regression was used to determine the independent associations between different variables and healthcare-seeking behaviors among canine-bite victims as well as attitudes of non-bitten study respondents. Results A total of 798 households were interviewed, capturing 100 canine-bite victims and a bite incidence of 2.3 per 100 person-years. Over half of bite victims actively sought medical treatment (56%), though very few received rabies post-exposure prophylaxis (3%). Bite victims who did not know or report the closest location where PEP could be received were less likely to seek medical care (p = 0.05). Respondents who did not report having been bitten by a dog with higher knowledge scores were more likely to respond that they would both seek medical care (p = 0.00) and receive PEP (p = 0.06) after a potential rabies exposure event. Conclusions There was varying discordance between what respondents who did not report having been bitten by a dog said they would do if bitten by a dog when compared to the behaviors exhibited by canine-bite victims captured in the KAP survey. Bite victims seldom elected to wash their wound or receive PEP. Having lower rabies knowledge was a barrier to theoretically seeking care and receiving PEP among not bitten respondents, indicating a need for effective and robust educational programs in the country.